Predicting Pumpability and Shootability of Crushed Aggregate Wet-Mix Shotcrete Based on Rheological Properties - Kyong-Ku Yun; Pangil Choi; Jung Heum Yeon (Advances in Materials Science and Engineering)
This study aims to estimate the pumpability and shootability of wet-mix shotcrete (WMS) made with crushed aggregates and various admixtures such as silica fume, fly ash, ground granulated blast furnace slag (GGBFS), metakaolin, and steel fiber based on rheological properties. The IBB rheometer was employed as an apparatus to measure the rheological properties of freshly mixed shotcrete such as flow resistance and torque viscosity. Results have shown that the use of silica fume and metakaolin led to satisfactory pumpability, whereas mixtures with fly ash and steel fiber failed to meet the pumping criteria at normal pump pressure. The build-up thickness, an indicator to represent shotcrete shootability, was predicted to vary between 68 and 218 mm, demonstrating that the use of admixtures resulted in a wide spectrum of shootability. In particular, the use of metakaolin was found to substantially increase the predicted build-up thickness only with a small replacement. The findings of this study are expected to be used as an easy-to-use guideline for estimating pumpability and shootability of WMS when no compliance testing data is available.